Reconstruction of Narcotics Rehabilitation Law in Indonesia: a Framework For Harmonization With Global Human Rights And Health Standards - Dharmaputra, Ngurah Suradatta; Latif, Abdul; Shodiq, Md. (Sahabat Publikasi, 2025)
The growing global consensus toward health- and rights-based approaches in drug policy has highlighted the limitations of punitive legal systems, especially in developing countries such as Indonesia. Despite legal provisions enabling rehabilitation for drug users, Indonesia’s narcotics law remains fragmented, discretionary, and misaligned with international standards set by the United Nations Office on Drugs and Crime (UNODC) and the World Health Organization (WHO). This normative legal research critically examines the gap between Indonesia’s legal framework on drug rehabilitation and international best practices, using comparative legal analysis and conceptual theory integration, including legal pluralism and therapeutic jurisprudence. Findings reveal that the Indonesian legal system lacks normative consistency, suffers from institutional overlap, and fails to uphold essential human rights protections in rehabilitation processes. Drawing from Portugal and Switzerland’s legal models, the study proposes a harmonization framework that incorporates voluntary treatment, role clarity, rights-based indicators, and inter-agency coordination. This paper contributes to both academic discourse and policy reform by offering a grounded pathway for aligning Indonesia’s rehabilitation law with evolving global standards.